LM22B-10 promotes corneal nerve regeneration through in vitro 3D co-culture model and in vivo corneal injury model. (1st July 2022) - Cui, Zekai; Liao, Kai; Li, Shenyang; Gu, Jianing; Wang, Yini; Ding, Chengcheng; Guo, Yonglong; Chan, Hon Fai; Ma, Jacey Hongjie; Tang, Shibo; Chen, Jiansu
Abstract: Corneal nerve wounding often causes abnormalities in the cornea and even blindness in severe cases. In this study, we construct a dorsal root ganglion-corneal stromal cell (DRG-CSC, DS) co-culture 3D model to explore the mechanism of corneal nerve regeneration. Firstly, this model consists of DRG collagen grafts sandwiched by orthogonally stacked and orderly arranged CSC-laden plastic compressed collagen. Nerve bundles extend into the entire corneal stroma within 14 days, and they also have orthogonal patterns. This nerve prevents CSCs from apoptosis in the serum withdrawal medium. The conditioned medium (CM) for CSCs in collagen scaffolds contains NT-3, IL-6, and other factors. Among them, NT-3 notably promotes the activation of ERK-CREB in the DRG, leading to the growth of nerve bundles, and IL-6 induces the upregulation of anti-apoptotic genes. Then, LM22B-10, an activator of the NT-3 receptor TrkB/TrkC, can also activate ERK-CREB to enhance nerve growth. After administering LM22B-10 eye drops to regular and diabetic mice with corneal wounding, LM22B-10 significantly improves the healing speed of the corneal epithelium, corneal sensitivity, and corneal nerve density. Overall, the DS co-culture model provides a promising platform and tools for the exploration of corneal physiological and pathological mechanisms, as well as the verification of drug effects in vitro . Meanwhile, we confirm that LM22B-10, as a non-peptide small molecule, has future potential in nerve wound repair. Statement of significance: The cornea accounts for most of the refractive power of the eye. Corneal nerves play an important role in maintaining corneal homeostasis. Once the corneal nerves are damaged, the corneal epithelium and stroma develop lesions. However, the mechanism of the interaction between corneal nerves and corneal cells is still not fully understood. Here, we construct a corneal stroma-nerve co-culture in vitro model and reveal that NT-3 expressed by stromal cells promotes nerve growth by activating the ERK-CREB pathway in nerves. LM22B-10, an activator of NT-3 receptors, can also induce nerve growth in vitro . Moreover, it is used as eye drops to enhance corneal epithelial wound healing, corneal nerve sensitivity and density of nerve plexus in corneal nerve wounding model in vivo . Graphical abstract: Image, graphical abstract